2013
DOI: 10.1007/s11356-012-1392-0
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of harmful algae in outer Oslofjorden monitored by microarray, qPCR, and microscopy

Abstract: Monitoring of marine microalgae is important to predict and manage harmful algal blooms. Microarray Detection of Toxic ALgae (MIDTAL) is an FP7-funded EU project aiming to establish a multi-species microarray as a tool to aid monitoring agencies. We tested the suitability of different prototype versions of the MIDTAL microarray for the monthly monitoring of a sampling station in outer Oslofjorden during a 1-year period. Microarray data from two different versions of the MIDTAL chip were compared to results fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Examples of these methods in studies of Alexandrium include the use of fluorescence in situ hybridization (John et al, 2003;Anderson et al, 2005;Touzet et al, 2010), real-time quantitative PCR (qPCR) (Galac et al, 2003;Galluzzi et al, 2004;Hosoi-Tanabe and Sako, 2005;Dyhrman et al, 2006) and DNA microarrays (Gescher et al, 2008;Galluzzi et al, 2011;Dittami et al, 2013). Each of these methods provide species-specific detection of the targeted toxic Alexandrium species.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of these methods in studies of Alexandrium include the use of fluorescence in situ hybridization (John et al, 2003;Anderson et al, 2005;Touzet et al, 2010), real-time quantitative PCR (qPCR) (Galac et al, 2003;Galluzzi et al, 2004;Hosoi-Tanabe and Sako, 2005;Dyhrman et al, 2006) and DNA microarrays (Gescher et al, 2008;Galluzzi et al, 2011;Dittami et al, 2013). Each of these methods provide species-specific detection of the targeted toxic Alexandrium species.…”
Section: Introductionmentioning
confidence: 99%
“…The supposed reason is that excessive labels in the target molecules might impede their accessibility to specific probes, hence producing less intensive hybridization signals. The DNA array technology is also disadvantaged by its high cost (Dittami et al, 2013). A rough estimation showed that BLPM is cheaper than the other two labeling methods.…”
Section: Discussionmentioning
confidence: 99%
“…One is to produce target molecules by PCR amplification using genomic DNA from target microalgae, with fluorescein added in or after the PCR (Gescher et al, 2008;Galluzzi et al, 2011), and the fluorescein-labeled PCR products are used for DNA array hybridization. The other is to directly label RNAs with fluorescein; the labeled products are then used for hybridization (Dittami et al, 2013;Kegel et al, 2013). Although a DNA array that involves direct RNA labeling could be used to quantify target cells, a relatively high detection limit may be a great disadvantage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The laser in a microarray scanner scans the slides and the hybridization pattern captured via fluorescent excitation indicates which species are present [60]. DNA microarrays, or phylochips as they have been termed, have been used to identify phytoplankton [63], toxic algae [64,65,66,67,68,69,70,71,72,73,74,75,76,77], bacteria [78,79,80,81,82,83,84], and eggs and larvae from fish species [85]. Phylochip ® , a universal microarray for all prokaryotic organisms is commercially available and circumvents the long analysis time to perform community analysis for the prokaryotes using other molecular tools.…”
Section: Molecular—cell-free Formatmentioning
confidence: 99%